Synthesis of TiO2/Graphene Quantum Dots as Photoanode to Enhance Power Conversion Efficiency for Dye-Sensitized Solar Cells - Hayder Hasan Ali, Majid R. Al-Bahrani (International Journal of Advanced Science and Technology, 2020)
Due to its superior characteristics, Graphene Quantum Dots (GQDs) are proposed for dye-sensitized solar cells (DSSCs). We added GQDs to TiO2 nanoparticles as a photoanode electrode (we used the doctor blade method) where the photoelectric properties were investigated in DSSCs. We prepared a solution of TiO2/GQDs with deionized water (DI) as precursors using the Hydrothermal method at a temperature of 160 ° C for 72 hours. Structural properties of TiO2 covered with GQDs were examined using SEM, XRD and TEM analyzes. When comparing devices manufactured in our laboratory, The J-V properties of the integrated solar cell for GQDs show PCE optimization of DSSC-3 with which we used TiO2/GQDs as photoanode. When we added GQDs to TiO2 (NPs) as photoanode with thickness of 12 µm, We managed to increase the density Short circuit current(Jsc) and power conversion efficiency (PCE) (from 17.72±0.03 to 18.98±0.05 mA cm-2) and (from 7.473±0.30 % to 9.047±0.04 %), respectively, for effective area (10mm2). The improvement in PCE of DSSC-3 this can be attributed to the rapid electron transport, enhanced electron collection at photoanodes and improved light harvesting efficiency. Studies show that when GQDs are added to TiO2, optical absorption in GQDs will increase, resulting in an improvement in the DSSC-3 device characteristics. As we noted in the above results for the device DSSC-3. Thus, the GQDs with unique structural and optical properties is a promising candidate substituting the conventional semiconductor quantum dots.